IMMACULATE CONCEPTION, INCUBATION PROTOCOLS, AND EGG CHARACTERISTICS OF THE GANGES SOFTSHELL TURTLE (ASPIDERETES GANGETICUS) - Whitaker, Nikhil (Contemporary Herpetology, 2006)
Reproductive biology of Aspideretes gangeticus was studied between 1986 and 2001. Clutchsize averaged 17.9 eggs and ranged between six to thirty-fi ve eggs. Egg length averaged 30.6 mm,egg width averaged 30.22 mm, and egg weight averaged 16.85 g. Clutch volume averaged 253.75ml. No signifi cant difference was observed in clutch size between dry and wet seasons. Of the variousincubation protocols tested, one that involved transitional temperatures of 28º – 31º C, to chilling at15º – 18º C, and then 23º – 26º C resulted in the highest hatching success. Aspideretes gangeticusexhibit two forms of development arrest during incubation, embryonic diapause early in incubation andembryonic aestivation in the latter trimester of incubation. The two Aspideretes gangeticus femalesthat produced clutches for the current study produced eggs with a high fertility percentage throughoutthe fi fteen years for which they stored sperm.